The Potency of Polyphenols Extract of Robusta Coffee Bean (Coffea robusta) on COX-2 Inhibition in Neutrophil Cells - Tantin Ermawati; Qurratul Aini Wahyu Pratiwi; Zahara Meilawaty; Happy Harmono (Jurnal Kedokteran Brawijaya, 2023)
Inflammation is a physiological response to various stimuli including infection and tissue injury. One cause of inflammation is gram-negative bacteria that release various toxins, e.g. lipopolysaccharide endotoxin (LPS). The first body defense response is neutrophils. Body defense response is expressed by the cyclooxygenase (COX) enzyme that functions to transform arachidonic acid into prostaglandin. Polyphenols extract from Robusta coffee bean is known to play an anti-inflammatory role, but the mechanism for inhibiting COX-2 remains unknown. This study aimed to determine the potential of polyphenols extracted from Robusta coffee beans on COX-2 inhibition in neutrophils exposed to E. coli LPS. The research design was experimental in vitro with a post-test-only control group design. The sample consisted of 6 treatment groups, neutrophil isolates was incubated in concentrations of Robusta coffee polyphenols extract of 3.13%, 6.25%, 12.5%, and 25% and exposed to E. coli LPS. Measurement of COX-2 expression was conducted using immunohistochemical methods. ANOVA and LSD test results showed COX-2 expression in the treatment groups, namely neutrophils which were incubated with Robusta coffee polyphenols extract and exposed to E. coli LPS, was lower than the neutrophil group exposed only to E. coli LPS. The conclusion of this study is that the polyphenols extract of the Robusta coffee bean can inhibit COX-2 expression on neutrophils exposed to E. coli LPS.